Rapeseed Oil and Sunflower Oil Diets Enhance Platelet In Vitro Aggregation and Thromboxane Production in Healthy Men when Compared with Milk Fat or Habitual Diets - Mutanen, Marja; Freese, Riitta; Valsta, Liisa M; Ahola, Irma; Ahlström, Antti (Thrombosis and Haemostasis, 1992)
In this highly controlled trial, 26 normolipidemic men (average age 28 years, range 18 to 60) were fed a baseline diet high in milk fat (MF) (fat 36% of energy, saturates 19%, monounsaturates 11%, polyunsaturates 4%), followed by a diet high in sunflower oil (SO) (fat 38% of energy, saturates 13%, monounsaturates 10%, polyunsaturates 13%) and another diet high in low erucic-acid rapeseed oil (RO) (fat 38% of energy, saturates 12%, monounsaturates 16%, polyunsaturates 8%). All diets were mixed natural diets with the same cholesterol contents. The baseline milk fat diet was given for 14 days and the oil diets for 24 days in a blind cross-over design. The platelet in vitro aggregation (slope %/min) induced by 1, 2 and 3 pM ADP and collagen (25 pg/ml PRP) was highly significantly (p <0.001) increased after both oil diets when compared with the results from the milk fat diet. The aggregation pattern determined by threshold collagen concentration confirmed increased collagen sensitivity of the platelets after the rapeseed oil diet (p <0.001). The enhancement of platelet aggregation was associated with increased in vitro platelet thromboxane production after the oil diets vs. the milk fat diet (p <0.05 after the sunflower oil diet and p <0.001 after the rapeseed oil diet).